Type D personality and other risk factors associated with acute coronary syndrome: a matched case-control study - Parajuli, Surya Bahadur; Shah, Prashant; KC, Heera; Khan, Sajjad Ahmed (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Acute coronary syndrome stands as a leading cause of cardiovascular-related fatalities. While several established risk factors are linked to acute coronary syndrome, the potential role of the type D personality trait remains a subject of interest, albeit lacking sufficient evidence in our local context, especially considering the influx of patients from Eastern Nepal. The objective of this study was to investigate the relationship between type D personality and other risk factors in association with acute coronary syndrome. Method: A matched case-control study was performed at a teaching hospital among 120 study participants from 9 June, 2023 to 30 March, 2024. Among them, 60 belong to the case group and 60 belong to the age and sex-matched control group. They were selected by consecutive sampling techniques. Ethical clearance was taken from the Institutional Review Committee of Birat Medical College Teaching Hospital. A structured questionnaires with DS-14 scale were used as study tools, collected data was entered in Microsoft Excel and analyzed by Statistical Package for the Social Sciences version 23. Result: This study involved 120 participants, comprising 60 cases of acute coronary syndrome and 60 age and sex-matched controls. Type D personality was significantly more prevalent in the acute coronary syndrome group, with an odds ratio of 3.16 (p=0.007). Individuals with acute coronary syndrome exhibited significantly higher rates of hypertension (p=<0.001), smoking (p=<0.001), dyslipidemia (p=0.020), and diabetes mellitus (p=<0.001) compared to controls. Conclusion: The study emphasizes a strong connection between acute coronary syndrome and Type D personality traits. Additionally, established risk factors like hypertension, smoking, dyslipidemia, and diabetes mellitus were also linked to acute coronary syndrome.